Validity of self-reported versus actual age in Nepali children and young people. (August 2016) - Heys, M.; Candler, T.; Costello, A.; Manandhar, D.S.; Viner, R.M.
Highlights: Self-reported age is a potential source of misclassification bias in International Surveys. We compare objectively recorded age with self-reported age at mean age 11.5 years in 3943 children in rural Nepal. There was high agreement between actual and self-reported age with an error rate of 7%.